ТИПОЛОГИЯ ТРУДНОСТЕЙ ПРИ ФОРМИРОВАНИИ ПИСЬМЕННОЙ РЕЧЕВОЙ КОМПЕТЕНЦИИ У СТУДЕНТОВ ВУЗОВ ПРИ ОБУЧЕНИИ КИТАЙСКОМУ ЯЗЫКУ - Жалилова, Н.Х. (SCIENCE and SOCIETY, 2023)
This article reviews the typology of difficulties in forming of the written speech competence among university students while teaching Chinese language. Analysis which was carried out helped to identify the errors encountered by students of level B2. During the analysis, the errors were divided into separate categories, which made it possible to consider each aspect of the typology in more detail.
Keywords: written speech competence; writing; difficulties; mistakes; category; Chinese language; foreign language